Acceptability of high yielding varieties among sugarcane farmers in the Province of Batangas - Catuira, Adel V. (2004)
The study was conducted to assess the acceptability of using high yielding varietiess (HYV) of sugarcane, based on the perspective of farmers in the Province of Batangas. thirty farmers engaged with the use of high yielding sugarcane varieties for Crop Year 2001-2002 were chosen as respondents. The descriptive method of investigation was used on the data gathered through a survey instrument.A majority of the sugarcane farmers uses the Phil 75-44 variety on their plantations even though it is not the top yield performer in the area. The Batangas farmers have a number of different HYVs to choose from as propagation and distribution programs are being carried out by organizations supporting the sugar industry inthe province. A dramatic change in the variety picture is occurring as could be seen in the downward trend in terms of the varieties milled. Old HYVs are slowly being replaced by new HYVs to further increase sugarcane productivity. Adaptability to the location still stands on the way for new HYVs to prove their worth as the successor of the dominant variety, Phil 75-44.The most preferred features of an HYV, accordingly ranked in order of importance are; 1) high in tonnage, 20 high sugar content, 3) good ratooning capacity, 4) fast growing, 5) gives a good number of tillers, 6) resistant to major pests and diseases, 7) self-trashing, 8) availability of planting materials and the lastly preferred feature, 10) location of the nursery. The first sixfeatures all add up to an increase in production, self-trashiness gives favor to the miller and the last three features give credit to the openness of the farmers in their acceptance of high yielding variety. Recommendations coming from the respondents must be given ample considerations such as the establishment of more nurseries for propagation, a systematic distribution scheme of new HYV's and a concerted effort of the different sectors involved in the further improvement of the sugar industry in the Province. Information drive must also be carried out in the Province to give the farmers enough knowledge on what new variety they can avail of and to ensure the sustainability of sugarcane farming in the area.
Research Paper (Mgt 299-Research Methods in Management). -- [Iloilo City] : UPV-CM, February 20,2004.